Territórios em disputa: a luta pela permanência das comunidades tradicionais no cerrado e a participação das mulheres nas ações sociais e na economia solidária em Buritizeiro-MG - Inácio, Jaqueline Borges (2021)
The purpose of this doctoral research is to understand the sociobiodiversity of the Cerrado and the ways of life of traditional communitiesintended by economic interests and strategies to remain in the demarcated territory for the implementation of the Extractive Reserve in the municipality of Buritizeiro, in the North of Minas Gerais, and the participation of women in social construction and solidarity economy. The time frame of this work covers the years from 1960 to 2020. The aim is to study the context of territorial dispute between traditional communities and agribusiness. It is important to analyze how the uses and extraction of natural resources occur, fundamental to the lives of people who depend on this territory to ensure their existence, which are (re) invented from their social-environmental knowledge and practices. The Cerrado is home to native and traditional peoples who have historically and culturally established their way of life as a result of their socio-cultural practices in/with the biome. These groups have been creating their knowledge and practices, establishing their territoriality and relations with nature`s cycles, and are part of the historical and cultural heritage of Brazil. Women play a fundamental role in social construction, in the conquest for Human Rights, in the development of the solidarity economy, and in the social actions performed during the COVID-19 pandemic, in partnership with the NGO “Movimento Graal Mulher no Brasil”. In the preparation of the thesis, a bibliographic survey was carried out, followed by readings and summaries of texts that discuss the sociobiodiversity of the Cerrado, the preservation of the biome, the creation of Sustainable Use Conservation Units: Extractive Reserves (RESEX) and Sustainable Development Reserves (RDS). In a second moment, we researched the websites related to public agencies such as Ministry of the Environment (MMA), Chico Mendes Institute of Biodiversity (ICMBio) and the National System of Conservation Units (SNUC), in order to obtain information about possible Sustainable Use Conservation Units, created or in the process of being created in the state of Minas Gerais. Then, readings were made in academic papers, and books of authors who studied the transformations of the North of Minas Gerais. In addition, we made photographic records, which will compose the collection of images of this work, through the observation of the landscapes that make up the historical and cultural scenario of the place. Fieldwork was carried out in the rural communities of Gerais do Calixto and Lança 1, at the headquarters of the Movimento Graal and at the City Hall, located in the urban area. We approached the researched people through informal conversation and in these places, we dialogued with them, addressing topics that we identified as the main ones, guided by a semi structured interview script. The motivation to talk about the themes were the socio-environmental events and their consequences for community life and its activities. We used the qualitative research methodology to elaborate this work, from the perspective of participant observation and life history, where the interviewees told us about their memories and life experiences as traditional populations living in/of the Cerrado.